Acute myocardial infarction treatments and outcomes in 6.5 million patients with a current or historical diagnosis of cancer in the USA. (4th December 2019) - Bharadwaj, Aditya; Potts, Jessica; Mohamed, Mohamed O; Parwani, Purvi; Swamy, Pooja; Lopez-Mattei, Juan C; Rashid, Muhammad; Kwok, Chun Shing; Fischman, David L; Vassiliou, Vassilios S; Freeman, Philip; Michos, Erin D; et al.
Abstract: Aims: The aim of this study is to evaluate temporal trends, treatment, and clinical outcomes of patients who present with an acute myocardial infarction (AMI) and have a current or historical diagnosis of cancer, according to cancer type and presence of metastases. Methods and results: Data from 6 563 255 patients presenting with an AMI between 2004 and 2014 from the US National Inpatient Sample (NIS) database were analysed. A total of 5 966 955 had no cancer, 186 604 had current cancer, and 409 697 had a historical diagnosis of cancer. Prostate, breast, colon, and lung cancer were the four most common types of cancer. Patients with cancer were older with more comorbidities. Differences in invasive treatment were noted, 43.9% received percutaneous coronary intervention (PCI) in patients without cancer, whilst only 21.0% of patients with lung cancer received PCI. Lung cancer was associated with the highest in-hospital mortality [odds ratio (OR) 2.71, 95% confidence interval (CI) 2.62–2.80], major adverse cardiovascular and cerebrovascular complications (OR 2.38, 95% CI 2.31–2.45), and stroke (OR 1.91, 95% CI 1.80–2.02), while colon cancer was associated with highest risk of bleeding (OR 2.82, 95% CI 2.68–2.98). Irrespective of the type of cancer, presence of metastasis was associated with worse in-hospital outcomes, and historical cancer did not adversely impact on survival (OR 0.90, 95% CI 0.89–0.91). Conclusion: A concomitant cancer diagnosis is associated with a conservative medical management strategy for AMI, and worse clinical outcomes, compared to patients without cancer. Survival and clinical outcomes in the context of AMI vary significantly according to the type of cancer and metastasis status. The management of this high-risk group is challenging and requires a multidisciplinary and patient-centred approach to improve their outcomes.